2020
DOI: 10.2147/cmar.s242903
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinicopathological Characteristics and Mutational Profiling of Adult T-Cell Lymphoblastic Lymphoma in a Chinese Population</p>

Abstract: The purpose of this study is to perform a retrospective analysis of disease outcomes and mutational profiles in patients with adult T-cell lymphoblastic lymphoma (T-LBL). Patients and Methods: A total of 43 patients were treated over a 9-year period at a single institution. The study examined treatment outcomes, clinical characteristics, and the use of circulating tumor DNA (ctDNA) and mutational profiling for patient diagnosis. Results: The estimated overall survival (OS) and progression-free survival (PFS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…A number of studies have shown that the levels of cfDNA/ctDNA may be associated with poor clinical prognosis indicators, and at least two studies have reported that the levels of cfDNA/ctDNA were significantly associated with age, B symptoms ( 34 , 35 ), disease stage ( 34 , 35 , 59 , 66 ), and the International Prognostic Index (IPI) score ( 34 , 35 , 37 , 59 , 61 ) in DLBCL. In T cell lymphoblastic lymphoma, studies have confirmed that ctDNA concentrations are associated with IPI scores ( 64 ). These indicators are highly correlated with poor prognosis.…”
Section: Lbs As Biomarkers For Prognosismentioning
confidence: 97%
See 2 more Smart Citations
“…A number of studies have shown that the levels of cfDNA/ctDNA may be associated with poor clinical prognosis indicators, and at least two studies have reported that the levels of cfDNA/ctDNA were significantly associated with age, B symptoms ( 34 , 35 ), disease stage ( 34 , 35 , 59 , 66 ), and the International Prognostic Index (IPI) score ( 34 , 35 , 37 , 59 , 61 ) in DLBCL. In T cell lymphoblastic lymphoma, studies have confirmed that ctDNA concentrations are associated with IPI scores ( 64 ). These indicators are highly correlated with poor prognosis.…”
Section: Lbs As Biomarkers For Prognosismentioning
confidence: 97%
“…In a National Cancer Institute (NCI) study, the ctDNA of 17 patients with DLBCL who progressed after complete remission (CR) was analyzed, and 15 were found to be positive for ctDNA before progression was detected (95). Chen et al monitored the ctDNA of 14 T cell lymphoblastic lymphoma patients after treatment and found that in the 2 cases that relapsed during the maintenance phase, ctDNA could be detected before recurrence (64). The time from the detection of ctDNA to clinical recurrence was 83 and 84 days in these patients (64).…”
Section: Lbs As Biomarkers In Disease Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in this study, the previously reported lymphoma-related genes [ 19 ] overlapped with the WES data in the Cancer Genome Atlas (TCGA) database, plus hot spot mutation genes, 69 genes were obtained for developing a panel for TMB estimation (panel-TMB), which could be used for overall survival (OS) analysis. We further validated our findings using data from the TCGA database.…”
Section: Introductionmentioning
confidence: 99%
“…Although many recent studies have focused on applications in hematological malignancies (8)(9)(10)(11)(12)(13), the results are still unclear. Therefore, we performed a meta-analysis to estimate the clinical application value in patients with hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%